2021
DOI: 10.1051/e3sconf/202124802006
|View full text |Cite
|
Sign up to set email alerts
|

R&D investment intensity, green energy technology innovation and construction firm growth performance

Abstract: Based on the data of listed construction companies in the jewelry manufacturing industry in 1994 from 2014 to 2017, this article uses the generalized least squares method to analyze the relationship between green energy technology innovation, construction enterprises’ growth performance and R&D investment intensity, and explores the impact of green energy technology innovation on construction enterprises’ growth performance and analyzes the moderating effect of R&D investment intensity. The empirical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…As the study found the problems of heteroskedasticity and autocorrelation, and to increase robustness and solve the problems of diagnostic tests, the study used feasible general least squares (FGLS) regression. FGLS measures the coefficients and covariance matrix for a multiple linear regression model in the presence of nonspherical innovations and an unknown covariance matrix Liu (2021). FGLS is more efficient than ordinary least squares (OLS) in the presence of heteroskedasticity and autocorrelation.…”
Section: Resultsmentioning
confidence: 99%
“…As the study found the problems of heteroskedasticity and autocorrelation, and to increase robustness and solve the problems of diagnostic tests, the study used feasible general least squares (FGLS) regression. FGLS measures the coefficients and covariance matrix for a multiple linear regression model in the presence of nonspherical innovations and an unknown covariance matrix Liu (2021). FGLS is more efficient than ordinary least squares (OLS) in the presence of heteroskedasticity and autocorrelation.…”
Section: Resultsmentioning
confidence: 99%
“…The results show that digital investment has a ∩ impact on green innovation, and strong digital integration capabilities play an important role in green development. However, the relationship between digitalization and green technology innovation has not been clarified due to the lack of a unified relationship between R&D investment and green technology innovation in current studies [19] .…”
Section: The Impact Mechanism Of Digital Transformation and Green Inn...mentioning
confidence: 99%